“If you can, change this system” - pregnant asylum seekers‘ perceptions on social determinants and material circumstances affecting their health whilst living in state-provided accommodation in Germany: a prospective, qualitative case study - Gewalt, Sandra Claudia; Berger, Sarah; Szecsenyi, Joachim; Bozorgmehr, Kayvan (BMC public health, 2019)
Background: Pregnant women and new mothers seeking asylum are highly vulnerable and have special needs, yet there is dearth of research related to this group in Germany. This paper reports on material circumstances and behavioural factors as social determinants of asylum seekers’ health during pregnancy and early motherhood. The study aim was to gain in-depth insights into these women’s experiences and perceived needs with a focus on material circumstances whilst living in state-provided accommodation in one federal state in Southern Germany. Methods: A qualitative, prospective approach was taken with individual semi-structured interviews of participants during pregnancy and up to the six-week postnatal assessment, aiming at interviewing each woman twice during pregnancy and once after giving birth. Two female interviewers performed interviews assisted by female professional interpreters on the telephone. Interviews were recorded digitally and transcribed verbatim. An inductive approach was taken to perform content analysis of interview material. Results: 21 interviews were performed with nine women seeking asylum in pregnancy and early motherhood. Content analysis of women’s perceived health-related needs revealed significant health challenges due to considerable constraints in two major themes each with associated categories: a) material circumstances and b) behavioural factors. Participants’ experiences of living conditions included significant challenges in terms of housing and neighbourhood quality e.g. poor hygiene standards with fear of disease and restless sleep due to threats of violence. Consumption potential was severely limited because of a minimal living allowance. Food was a major preoccupation for all participants. Catering services in state-provided accommodation were perceived as unsatisfactory and neglecting religious practices. Institutional food provided adequate calorific intake but participants reported loss of appetite due to bland food, limited variety, little choice and unfamiliar tastes. Self-catering was prohibited further exacerbating this problem. Conclusions: Pregnant asylum seekers and new mothers living in state-provided accommodation experienced major restrictions related to material circumstances in this study. Key results identified housing and neighbourhood quality, consumption potential and nutrition as social determinants of health which women perceived to adversely affect their health, especially during pregnancy and early motherhood.
Gesehen am 22.07.2019